THE EFFECTIVENESS OF THE USE OF PEAT ASH IN THE COMPOSITION OF PEAT NUTRIENT SOIL FOR GROWING TOMATO SEEDLINGS - Tatyana ANISIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article presents the results of studies on the use of nutritious soils based on peat and peat ash for the cultivation of tomato seedlings (Solanum lycopersicum L.). It was found that the most effective was the use of peat-ash compost with a ratio of components 1:4 and peat-ash-lupine compost (1:1:2). The results obtained confirmed their positive influence on the biomass growth of tomato plants, foliage and stem length.